Parents' Understanding About Breast Milk Complementary Foods (MP-ASI) in Harjobinangun Village Grabag District Purworejo Regency - Agesti, Riyan; Mukminin, Amirul (Jurusan PGPAUD FIP UNNES, 2018)
Understanding is the ability of a person to know and understand something about the meaning or concept, situation, and facts by understanding the meaning contained in it. The examined problem in this study is how parents understand about MP-ASI (breast milk complementary foods) in Harjobinangun Village, Grabag District, Purworejo Regency and how the role of health workers in creating parents' understanding of MP-ASI. This study aims to find out how parents understand about MP-ASI in Harjobinangun Village, Grabag District, Purworejo Regency, and find out the role of health workers in creating understanding among parents about MP-ASI. This research is a qualitative research. The approach in this study is a case study approach. The subjects in this study are 4 people. Data collection methods are interviews, observation, and documentation. The data analysis technique is an interactive model. The data validity technique is triangulation. The results of data analysis collected from the field, parents' understanding of MP-ASI in Harjobinangun Village, Grabag District, Purworejo District, is that parents' understanding of MP-ASI is still lacking. This is because parents do not feed children according to the four-star menu. Parents feed children only with rice and side dishes or rice and vegetables. In addition, there are still elderly people who feed children with packaged children's food and parents also rarely give fruits to children. The role of health workers in creating parents' understanding of MP-ASI is as a motivator, facilitator, counselor, and resource.